Prevalence of nonfounder BRCA1/2 mutations in Ashkenazi Jewish patients presenting for genetic testing at a hereditary breast and ovarian cancer center - Frey, Melissa K.; Kopparam, Rohini V.; Ni Zhou, Zhen; Fields, Jessica C.; Buskwofie, Ama; Carlson, Ann D.; Caputo, Thomas; Holcomb, Kevin; Chapman‐Davis, Eloise (Cancer, 2019)
Background Genetic assessment in Ashkenazi Jewish (AJ) patients often is limited to BRCA1/2 founder mutation testing. With access to time‐efficient and cost‐efficient multigene panel testing, some advocate expanding genetic testing in this population. However, to the best of the authors’ knowledge, rates of nonfounder BRCA1/2 mutations and mutations in cancer‐associated genes other than BRCA1/2 among AJ are not known. In the current study, the authors sought to assess the prevalence of mutations other than BRCA1/2 founder mutations among AJ patients undergoing genetic assessment. Methods The authors reviewed the medical records for all AJ patients who underwent genetic assessment at a single institution between June 2013 and December 2016. Mutations were categorized as 1) BRCA1/2 AJ founder mutations (BRCA1 185delAG, BRCA1 5382insC, or BRCA2 6174delT); 2) nonfounder BRCA1/2 mutations; or 3) mutations in non‐BRCA1/2 cancer‐associated genes. Results A total of 732 AJ patients underwent genetic assessment. Of these, 371 patients (51%) had a personal history of breast or ovarian cancer, 540 patients (73.8%) had a family history of breast cancer, and 132 patients (18%) had a family history of ovarian cancer. In the study population, 101 patients (13.8%) were found to have a pathogenic mutation, 78 patients (10.7%) had a BRCA1/2 founder mutation, 3 patients (0.4%) had a nonfounder BRCA1/2 mutation, and 20 patients (2.7%) had a mutation in a non‐BRCA1/2 cancer‐associated gene. Non‐BRCA1/2 cancer‐associated genes harboring mutations included RAD51D, TP53, mutS homolog 6 (MSH6), checkpoint kinase 2 (CHEK2), adenomatous polyposis coli (APC), and Fanconi anemia group C protein (FANCC). Conclusions Among AJ patients found to have a pathogenic mutation on genetic assessment, approximately 22.8% had a mutation that would be missed with BRCA1/2 AJ founder mutation testing. Comprehensive multigene panel sequencing can provide clinically relevant genetic information for AJ patients and should be considered for genetic assessment in this population. Traditionally, genetic testing in Ashkenazi Jewish patients has targeted BRCA1/2 founder mutations. In the current study cohort, it is reported that approximately 23% of pathogenic mutations would be missed with BRCA1/2 founder mutation testing alone, suggesting that comprehensive multigene sequencing may be a useful strategy in this population.